The development of isohyet map for Pahang State using Kriging method - Athirah, Zulkifli (2016)
Peninsular Malaysia has uneven topographical and geographical landscapes hence giving it uneven distribution of monthly rainfall quantity throughout the country. Pahang is one of the states in the Peninsular Malaysia where the total rainfall for every month was different and subjected to regular monsoon season especially the North East Monsoon. The aim goal of this study is to produce the isohyets maps of rainfall pattern and intensity of 11 districts in Pahang via software called ArcGIS 10.2 using Kriging method. The rainfall data was collected from various rainfall stations that were set up by the Department of Irrigation and Drainage Malaysia (DID) from 2001 until 2015. From the stimulated isohyets map, the maximum and minimum rainfalls for 11 districts in Pahang were analyzed as well as seasonal and regional trends revealed three major regions in Pahang that is high-elevated, inland, and coastal region. The seasonal and regional trends of rainfall pattern have been examined. The seasonal distribution of rainfall shows that from November to March is higher which may due to the Northeast monsoon effect over Pahang. Meanwhile, for regional distribution, the highest average value occurence of rainfall are over coastal areas compared to inland areas. From the monthly isohyet maps for duration 15 years, it showed that the highest average rainfall for monthly was recorded in the eastern area, which is at Rompin area (442.48 mm) in December. Meanwhile, the western region at Temerloh area (51.44 mm) displayed low average rainfall, in February. For the annual average rainfall showed that the highest annual average rainfall was recorded at Rompin area (2340.38 mm) and the lowest annual average rainfall was detected at Temerloh area (1364.39 mm). Overall, from the analysis, the changes of rainfall pattern in Pahang state influenced by monsoon winds, weather climate, and topography & geology.